2010
DOI: 10.1111/j.1468-4446.2010.01338.x
|View full text |Cite
|
Sign up to set email alerts
|

But the kids are okay: motherhood, consumption and sex work in neo‐liberal Latin America

Abstract: Although sex work remains highly stigmatized around the world, its relatively high value (when compared to other kinds of work available for low-income women) allows sex workers to attain some level of economic, if not social, mobility. This article challenges the idea that sex work in 'third world' settings is always about mere subsistence. Instead, it suggests that sex workers in Costa Rica's tourism sector work to survive, but they also demonstrate significant personal ambition and aim not only to increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 33 publications
2
28
1
1
Order By: Relevance
“…This is done by most of the articles in the two Costa Rican newspapers considered in our study. This kind of degrading treatment applies not only to sex workers, but also to other minorities (Igartua, 2004) Like Bustos (2010) we found that the media presents sex workers as being outside the law and in conflict with other social actors, but we disagree with Bustos on her acceptance of the myth of the "exploitation view" of sex work, which has been shown to be a belief without ground for the current sex work scene in Costa Rica Ramírez et al, 2009;Rojas et al, 2009;Rivers-Moore, 2010;Monge et al, 2011).…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…This is done by most of the articles in the two Costa Rican newspapers considered in our study. This kind of degrading treatment applies not only to sex workers, but also to other minorities (Igartua, 2004) Like Bustos (2010) we found that the media presents sex workers as being outside the law and in conflict with other social actors, but we disagree with Bustos on her acceptance of the myth of the "exploitation view" of sex work, which has been shown to be a belief without ground for the current sex work scene in Costa Rica Ramírez et al, 2009;Rojas et al, 2009;Rivers-Moore, 2010;Monge et al, 2011).…”
Section: Discussioncontrasting
confidence: 39%
“…Despite social repression, some women practice sex work and other activities associated with their sexuality when it is their only option, while others freely chose this kind or work among other options because it pays well (Rojas, Monge-Nájera, Rivers-Moore 2010). In a related area, glamour and nude modeling, the way in which women describe their bodies and personalities reflect their belief that they can use their own sexuality as a road to success beyond the traditional stereotype of "dependent females" (Monge & Vega, 2011).…”
Section: Presentation Of Sex Work In Two Costa Rican Newspapersmentioning
confidence: 99%
“…More recent data show that women who do sex work have incomes that are far superior to those they would have as cleaning ladies, receptionists, cheap laborers in the "maquila" sector or other jobs befitting their educational level ). A recent study argues convincingly that sex work enables some Costa Rican women not only to subsist, but also to give themselves and their families a relatively high standard of living (Rivers-Moore, 2010). …”
Section: Palabras Clavementioning
confidence: 99%
“…A big emphasis on Costa Rica's sex tourism and child exploitation scene has caused alarm in other countries, and has raised the question of trafficking. However, several studies have reported that most female and male sex workers freely choose this line of activity and work as independent contractors (Rivers-Moore, 2009, 2010, 2013.…”
Section: Introductionmentioning
confidence: 99%